WHAT ATTRACTS RURAL YOUTH TO FARMING? EVIDENCE FROM CENTRAL JAVA - Adiyana Saputra; Istiqomah Istiqomah; Goro Binardjo (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The phenomenon of aging farmers has received severe concern in many countries due to its adverse impact on agricultural productivity. Therefore it is essential to investigate the determinants of farmer regeneration.  This study aims to analyze the effect of parents' landholding, education, motor vehicle ownership, and parents' desire on rural youth's interest in becoming farmers. This study is different from the previous ones by adding parents’ desire for their children to become a farmer as a new independent variable. The population of this study consists of rural youth aged 15-24 years whose parents are farmers. Cluster sampling was used to select 44 respondents. The data was then analyzed by multiple linear regression. The results show that parents’ landholding and parents’ desire that their children become farmers have a positive effect, education has a negative impact, and ownership of motor vehicles indicates no effect on the interest of youth to become farmers. These results imply that to increase the interest of the rural child to become farmers, the welfare aspect is a crucial consideration. Therefore, government, schools, and parents need to emphasize understanding the strategic role of agriculture in the economy and make it a promising source of livelihood.